Transcriptome-based analysis of the effects of compound microbial agents on gene expression in wheat roots and leaves under salt stress - Ji, Chao; Liang, Zengwen; Cao, Hui; Chen, Zhizhang; Kong, Xuehua; Xin, Zhiwen; He, Mingchao; Wang, Jie; Wei, Zichao; Xing, Jiahao; Li, Chunyu; Zhang, Yingxiang; et al. (Frontiers in Plant Science, 2023)
Introduction: Salt stress inhibits the beneficial effects of most plant growth-promoting rhizobacteria. The synergistic relationship between beneficial rhizosphere microorganisms and plants helps achieve more stable growth-promoting effects. This study aimed 1) to elucidate changes in gene expression profiles in the roots and leaves of wheat after inoculation with compound microbial agents and 2) to determine the mechanisms by which plant growth-promoting rhizobacteria mediate plant responses to microorganisms. Methods: Following inoculation with compound bacteria, transcriptome characteristics of gene expression profiles of wheat, roots, and leaves at the flowering stage were investigated using Illumina high-throughput sequencing technology. Gene ontology (GO) function and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed on the genes that were significantly differentially expressed. Results: The expression of 231 genes in the roots of bacterial preparations (BIO) -inoculated wheat changed significantly (including 35 upregulated and 196 downregulated genes) compared with that of non-inoculated wheat. The expression of 16,321 genes in leaves changed significantly, including 9651 upregulated genes and 6670 downregulated genes. The differentially expressed genes were involved in the metabolism of carbohydrates, amino acids, and secondary compounds as well as signal transduction pathways. The ethylene receptor 1 gene in wheat leaves was significantly downregulated, and genes related to ethylene-responsive transcription factor were significantly upregulated. KEGG enrichment analysis showed that linoleic acid metabolism expression was highest in the roots, and the expression of photosynthesis-antenna proteins was the highest in leaves. After inoculation with a complex biosynthesis agent, the phenylalanine ammonia lyase (PAL) gene of the phenylpropanoid biosynthesis pathway was upregulated in wheat leaf cells while 4CL, CCR, and CYP73A were downregulated. Additionally, CYP98A and REF1 genes involved in the flavonoid biosynthesis pathway were upregulated, while F5H, HCT, CCR, E2.1.1.104, and TOGT1-related genes were downregulated. Discussion: Differentially expressed genes may play key roles in improving salt tolerance in wheat. Compound microbial inoculants promoted the growth of wheat under salt stress and improved disease resistance by regulating the expression of metabolism-related genes in wheat roots and leaves and activating immune pathway-related genes.